Diet associations with nonalcoholic fatty liver disease in an ethnically diverse population: the Multiethnic Cohort - Noureddin, Mazen (Hepatology, 2020)
Epidemiological data on dietary risk factors for NAFLD from population-based studies, particularly in an ethnically diverse population, are scarce. We examined dietary factors in relation to NAFLD risk in African Americans, Japanese Americans, Latinos, Native Hawaiians, and whites in the Multiethnic Cohort (MEC). A nested case-control analysis was conducted within the MEC, a large prospective study with >215,000 older-adult participants in Hawaii and California. NAFLD was identified using Medicare claims data, and controls were selected among participants without liver disease and individually matched to cases by birth year, sex, ethnicity, and length of Medicare enrollment. Diet was assessed at baseline via a validated quantitative food frequency questionnaire. Diet-NAFLD associations were quantified by odds ratios (ORs) and 95% confidence intervals (CIs) using multivariable conditional logistic regression. The study consisted of 2,974 NAFLD cases (518 with cirrhosis; 2,456 without cirrhosis) and 29,474 matched controls. Red meat (P trend=0.010), processed red meat (P trend= 0.004), poultry (P trend= 0.005) and cholesterol (P trend= 0.005) intakes were positively associated with NAFLD, while dietary fiber intake (P trend=0.003) was inversely associated with risk. Stronger associations were observed between red meat and cholesterol and NAFLD with cirrhosis than without cirrhosis (P heterogeneity ≤0.014). Conclusion: Dietary factors are independently associated with NAFLD and NAFLD-related cirrhosis in a multiethnic population. Decreasing the consumption of cholesterol, red and processed meat and poultry and increasing consumption of fiber may reduce the risk for NAFLD and related advanced liver disease.